MAGAZINE «OTECHESTVENNYE ZAPISKI » IN THE HISTORY OF RUSSIAN CULTURE OF THE 19TH CENTURY - N. V. Shevtsov (Концепт: философия, религия, культура, 2019)
The literary magazine «Otechestvennye Zapiski» legitimately belongs to the realm of the most known and reputable periodicals in the history of Russian journalism. Its publishers did everything possible to refine the journalistic style of its content and to turn each issue or, a book, as they used to call them, into high-quality classical thick literary magazines. The magazine published articles and stories of various genres. All of them stood out in terms of the high-quality writing. Both, up-and-coming and established authors dreamed of a publication there. At the same time, all of them realized that it was crucial to write something special for «Otechestvennye Zapiski», something not to be found in any other magazine. For many years, the magazine had a reputation of journalism training school. Yet, not only had it shaped outstanding journalists. Many up-and-coming writers became famous after the magazine featured their first works. Those, who we call today the classics of Russian literature, were among them. The magazine discovered Mikhail Lermontov to the world by being the first publisher of his short novels «Bela», «Fatalist», and «Taman» which later became parts of the novel «A Hero of Our Time». Many poems of Lermontov found the readers through «Otechestvennye Zapiski». Some of the early works of Nikolay Gogol and Fyodor Dostoyevsky were first featured there. It was this magazine, where young Turgenev gave his early poems as well. Plays of Alexander Ostrovsky went to the stages of the leading theaters shortly after being published in «Otechestvennye Zapiski». Taking advantage of the glory of a brilliant literary and artistic magazine, “Otechestvennye Zapiski” made a great contribution to the Russian culture. From the first years of its existence, articles on the newly opened private art galleries, numismatic collections, libraries, and various art exhibitions began to appear on its pages. From the very beginning of its publication and up to its closure, the journal carried out an important educational mission.